Hi dear Jamie. well it seems am too late. no problem....
x^2+3x-8=x^2-x+11
x^2+3x-8 -( x^2-x+11 ) = 0
x^2+ 3x -8 - x^2 + x - 11 = 0
[x^2 - x^2] + [ 3x +x] + [ -8 - 11] = 0
0 + 4x - 19 = 0
4x - 19 = 0
4x = 19
x = 19/4
x = 4.75
Good Luck Darling.
2006-09-23 06:15:31
·
answer #1
·
answered by sweetie 5
·
2⤊
0⤋
step 1 : combine like terms and simplify
x^2 +3x-8 -x^2 +x -11 = 0
4x -19 = 0
step 2: isolate the vairiable and sip,lify
4x = 19
x = 19/4
2006-09-23 05:46:53
·
answer #2
·
answered by Brian F 4
·
0⤊
1⤋
cancel out the x^2, you get,
+3x-8=-x+11
therefore,
4x=19
x= 19/4
2006-09-23 05:49:17
·
answer #3
·
answered by superlaminal 2
·
1⤊
0⤋
you get all the variables on mone side and all the nombers on the other and do whatever math you need to do....
2+3x-8=2-x+11
-x -x
2+2x-8=2+11
-6+2x=13
+6 +6
2x=19
divide 19 by 2 and you get x=9and one half
2006-09-23 05:42:09
·
answer #4
·
answered by allison m 2
·
0⤊
2⤋
x^2 + 3x - 8 = x^2 - x + 11
subtract x^2, then add x, then add 8 to both sides
4x = 19
x = (19/4)
ANS : x = (19/4)
2006-09-23 07:11:23
·
answer #5
·
answered by Sherman81 6
·
1⤊
2⤋
x^2+3x-8=x^2-x+11
-x^2+x-11=-x^2+x-11
================
4x-19=0
x=19/4
2006-09-23 05:06:22
·
answer #6
·
answered by fcas80 7
·
0⤊
0⤋
x^2+3x-8=x^2-x+11
3x-8=-x+11
4x=11+8
4x=19
x=19/4
2006-09-23 05:05:09
·
answer #7
·
answered by locuaz 7
·
0⤊
0⤋
divide both sides by x^2...is a good place to start.
you have:
3x-8=x-+11
the rest is easy.
2006-09-23 05:37:32
·
answer #8
·
answered by Mark H 1
·
0⤊
3⤋